Adaptive Traffic Signal Control Mechanism for Intelligent Transportation Based on a Consortium Blockchain - Zhang, Xiaohong; Wang, Di (IEEE access, 2019)
The development of vehicular ad-hoc networks (VANETs) has facilitated adaptive traffic signal control for intelligent transportation. In this paper, we proposed the traffic signal control mechanism based on a consortium blockchain, which has saved plenty of financial and material resources. It has solved the centralization problems and minimized the high degree of human intervention in the process of traffic signal light management. As a road is congested, the vehicle forwards road condition messages. The traffic department ( TD ) adjusts the signal light duration to allow the synergistic optimization management, and control the traffic vehicle status through a smart contract. In addition, we propose a credibility mechanism to effectively prevent vehicles from broadcasting mendacious messages and malicious requests, thereby enhancing the credibility of vehicles and providing a secure and trustworthy communication environment for the VANETs. It is hazardous for vehicles to send plaintext messages in an open environment because their privacy and security are threatened. Thus, we utilize ElGamal encryption and group signature algorithm to guarantee the confidentiality, privacy, and non-repudiation of any information. The safety analysis and performance evaluation demonstrate that the scheme is feasible and valid, and it can facilitate the adaptive control of traffic signal lights.